GC-MS ANALYSIS OF PETROLEUM ETHER AND ETHANOL LEAF EXTRACTS FROM ABRUS PRECATORIUS LINN - V.GNANAVEL; A. MARY SARAL (International Journal of Pharma and Bio Sciences, 2013)
The leaves of Abrus precatorius have enormous medicinal importance and are therefore used in the treatment of coughs, flu, eye infection, inflammation, skin disease, bacterial and viral infections. In the present study, petroleum ether and ethanol leaf extracts from Abrus precatorius were subjected to GC-MS analysis to study the important phytochemical constituents responsible for the above reported pharmacological activities. The crude extracts of petroleum ether and ethanol were obtained by immersion method. The preliminary phytochemical analysis of various extracts confirmed the presence of secondary metabolites like alkaloids, flavonoids, saponins, tannins, triterpenes, carbohydrates, proteins, glycosides and steroids. The GC-MS analysis of petroleum ether leaf extract from Abrus precatorius revealed the presence of nine phytocompounds: n-hexadecanoic acid (1), [1,1-bicyclopropyl]-2-octanoic acid, 2-hexyl-methyl ester (2), Isopropyl linoleate (3), Isopropyl linoleate (4), 9,12-octadecadienoic acid, ethyl ester (5), Hexadecanoic acid, 2-hydroxy-1-[hydroxymethyl] methyl ester (6), 9,12,15-octadecatrienoic acid (Z,Z,Z)-2,3-dihydroxypropylester (7), 9,12-octadecadienoic acid (Z,Z)-2,3-dihydroxypropyl ester (8), Octadecanoic acid, 2-hydroxy-1-(hydroxymethyl)ethyl ester (9). The GC-MS analysis of ethanol leaf extract from Abrus precatorius revealed the presence of ten phytocompounds: 1,2 Benzene dicarboxylic acid, butyl cyclohexyl ester (1), Hexadecanoic acid, ethyl ester (2), 9,12, octadecadienoic acid ethyl ester (3), Phytol (4), Oleic acid (5), 9,12-octadecadienoic acid (Z,Z)-2,3-dihydroxypropyl ester (6), 9,12-octadecadienoic acid (Z,Z)-2,3-dihydroxypropyl ester (7), Hexadecanoic acid, 2-hydroxy-1-(hydroxymethyl)ethyl ester (8), 9,12-octadecadienoic acid(Z,Z),2-hydroxymethyl)ethyl ester (9), Cyclopropanebutanoic acid, 2- [[2- [[2- [[2-pentylcyclopropyl] methyl] cyclopropyl]methyl]cyclopropyl]methyl]-methyl ester (10).